2014
DOI: 10.1186/1479-5876-12-s2-s9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support Systems (CDSS) for preventive management of COPD patients

Abstract: BackgroundThe use of information and communication technologies to manage chronic diseases allows the application of integrated care pathways, and the optimization and standardization of care processes. Decision support tools can assist in the adherence to best-practice medicine in critical decision points during the execution of a care pathway.ObjectivesThe objectives are to design, develop, and assess a clinical decision support system (CDSS) offering a suite of services for the early detection and assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…PMs could be integrated with other information to build clinical diagnosis support systems, which are already implemented in some areas [Samarghitean and Vihinen, ; Velickovski et al. ; Jabez Christopher et al. ].…”
Section: Applications Of the Pmmentioning
confidence: 99%
See 1 more Smart Citation
“…PMs could be integrated with other information to build clinical diagnosis support systems, which are already implemented in some areas [Samarghitean and Vihinen, ; Velickovski et al. ; Jabez Christopher et al. ].…”
Section: Applications Of the Pmmentioning
confidence: 99%
“…PMs could be integrated with other information to build clinical diagnosis support systems, which are already implemented in some areas [Samarghitean and Vihinen, 2008;Velickovski et al 2014;Jabez Christopher et al 2015]. In addition to the diagnostic level of pathogenicity, additional thresholds could be implemented.…”
Section: Figurementioning
confidence: 99%
“…The argument for decisions in wound treatment were expressed using these classes (wound-bed appearance, stage, exudate level, treatment, frequency, cleansing solution, and instructions), and their variables using rule-based reasoning logical operations of IF-AND-THEN model in the order of antecedent-to-consequent actions [4,10]. The selection of IF and AND corresponded with the wound attributes (wound-bed appearance, stage, exudate level, and classification), and served as the "antecedents" (input).…”
Section: Determining the Decision Flow For The Pi-cdss Constructmentioning
confidence: 99%
“…An iterative and incremental development for a comprehensive CDSS is adopted, which could support knowledge-based reasoning for chronic-wound management [10,20]. The study project started with the construct of only the PI-CDSS.…”
Section: Knowledge Evaluationmentioning
confidence: 99%
“…Studies have reported the effectiveness of utilizing CDSS in health conditions such as asthma 30 , chronic obstructive pulmonary disease 31 , pain therapy 32 , cardiovascular disease 33 , breast cancer detection 34 and a host of other health conditions with the exception of pancreatic cancer. The notion of CDSS has been around for the past 30 years however, implementation and acceptance of using CDSS in health care settings are still at the bare minimum.…”
Section: Introduction To the Problemmentioning
confidence: 99%